2018
DOI: 10.1016/j.biortech.2017.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal liquefaction of microalgae over transition metal supported TiO2 catalyst

Abstract: HighlightsNi/TiO2 improves the hydrothermal liquefaction of Nannochloropsis.A reaction temperature of 300 °C leads to the best liquefaction effect.The viscosity, TAN, and boiling point distribution of biocrude changed with Ni/TiO2.Adding Ni/TiO2 results in more acids and hydrocarbons in biocrude.The Ni/TiO2 catalyst performs a good reproduction ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(43 citation statements)
references
References 49 publications
2
40
0
1
Order By: Relevance
“…These high yields are linked to the low amounts of solid residue obtained in the catalytic processes (0.50 wt% to just under 6 wt%) in comparison with the solid yield in the thermal reaction (7.60 ± 0.70 wt%). This increase in the liquefied fraction and a low yield of the solid residue was observed previously in the HTL of rice husk and microalga Nannochloropsis with the same type of catalysts [37,40]. Table 3 shows the elemental analysis, HHV and energy recovery (ER) of the biocrudes obtained with the metal oxide-catalysed HTL and the non-catalysed process.…”
Section: Effects Of Catalysts On the Yields Of Hydrothermal Liquefactsupporting
confidence: 70%
“…These high yields are linked to the low amounts of solid residue obtained in the catalytic processes (0.50 wt% to just under 6 wt%) in comparison with the solid yield in the thermal reaction (7.60 ± 0.70 wt%). This increase in the liquefied fraction and a low yield of the solid residue was observed previously in the HTL of rice husk and microalga Nannochloropsis with the same type of catalysts [37,40]. Table 3 shows the elemental analysis, HHV and energy recovery (ER) of the biocrudes obtained with the metal oxide-catalysed HTL and the non-catalysed process.…”
Section: Effects Of Catalysts On the Yields Of Hydrothermal Liquefactsupporting
confidence: 70%
“…Moreover, the energy recovery corroborates with biocrude yields. In this study, ER were 71% for M1, 67% for M2, 75% for M3, 89% for M4 and 86% for M5 and were within the range of reported scientific literature [3,5,27]. Skakya et al, [5] reported ER of 47% for Chlorella sp., 78% for Scenedesmus sp.…”
Section: Effect Of Separation Protocols On Energy Densitysupporting
confidence: 51%
“…when operating at 220 o C to 320 o C at 30min. Wang et al, [3] reported ER of 43% to 61% from HTL of Nannochloropsis sp. at reaction temperature of 300 o C and 30min time with different catalysts.…”
Section: Effect Of Separation Protocols On Energy Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Conversion of algae in the presence of heterogeneous catalysts might cover the deficiency of homogeneous catalysts. Commonly, heterogeneous catalysts include zeolites (e.g., H-ZSM-5), supported metal catalysts (Pt/C), and other metal oxide supported catalysts (e.g., sulfide CoMo/Al 2 O 3 and Ni/TiO 2 ) [117][118][119]. These materials have strong activity for bonds cleavage, resulting in facilitation of macromolecule degradation and conversion of oxygenates and nitrogenates to high-grade hydrocarbons.…”
Section: Catalytic Htl With Heterogeneous Catalystsmentioning
confidence: 99%